Decent work in a seascape of livelihoods: Regional evaluation of the shrimp and groundfish fishery of the Guianas-Brazil shelf. (October 2022) - Lout, Gabrielle; Fitzpatrick, Juno; Garcia Lozano, Alejandro J.; Finkbeiner, Elena
Abstract: With growing evidence of labor violations and exploitative working conditions in fisheries, ensuring decent work is imperative to protect fishers and fishworkers in the global seafood sector. This study provides the first evaluation of decent work in a shared, transboundary fishery – the shrimp and groundfish fishery of the Guianas-Brazil Shelf. Decent work in fisheries has gained increasing attention and research, yet gaps exist in our understanding of the elements of decent work, how we evaluate it, and how to enable decent work. To date, there has been limited analysis of decent work in a range of geographies and diverse fisheries contexts, including small-scale fisheries and transboundary fisheries. This study will address this gap by evaluating decent work, utilizing a new fishery-specific, holistic evaluation framework drawing from existing frameworks including the ILO Work in Fishing Convention (C188), the Monterey Framework for Social Responsibility, and the FAO Voluntary Guidelines for Securing Sustainable Small-Scale Fisheries. This evaluation details country-level challenges that put fishers and fishworkers at risk in their occupation, including illegal fishing, vessel safety, and worker representation. This paper concludes with recommendations, to be advanced with a transboundary, regional approach, to ensure decent work and strengthen existing progress, including 1) addressing widespread illegal activities, 2) adopting fisheries-specific standards like C188, 3) implementing and enforcing policies at the country and regional level, and 4) ensuring worker representation and participation leveraging cooperatives and collectives. Highlights: Labor violations and exploitative working conditions are well-documented in global fisheries. There has yet to be a holistic approach to evaluate decent work. We offer an evaluative framework built from diverse human rights instruments and guidance. We pilot this framework in the transboundary fishery of the Guianas-Brazil Shelf Key issues identified in the fishery includeillegal fishing, poor vessel safety, and limited worker representation.